Prevalence and Identification of Bacillus cereus in Some Dried Dairy Products Focuses on Its Toxigenic Genes - Sidiq , Yahya Anwar; Mohammed , Othman Abdulrahman (Kurdistan Journal of Applied Research, 2025)
Bacillus cereus is a spore-forming, toxin-producing bacterium. It has significant food safety risks, especially in dried dairy products, including powdered and infant milk. This may pose a risk to the consumers. The current study aimed to show the prevalence and toxigenic potential of B. cereus in 134 milk samples. They were collected randomly from food stores and various sale points in the local markets from Sulaymaniyah and Halabja provinces between November 2024 and May 2025. Bacterial isolation was performed using Mannitol egg Yolk Polymyxin (MYP) agar. The isolates were then confirmed by biochemical assays, VITEK 2 (BCL), and Polymerase Chain Reaction (PCR) amplification of gyrB and 16S rRNA genes. Phylogenetic analysis revealed close genetic clustering of the isolates with reference strains of B. cereus, B. thuringiensis, and B. tropicus. Antimicrobial susceptibility testing using the disk diffusion method presented complete resistance to β-lactam antibiotics. However, all isolates remained susceptible to ciprofloxacin, tetracycline, erythromycin, and vancomycin. Of the tested samples, B. cereus was detected in 48% of different types of powdered milk and 11.7% of infant milk samples. Virulence gene analysis displayed high prevalence rates of enterotoxins: nheA (100%), nheB (80.76%), cytK (86.53%), hblA (75%), and hblC (88.46%). While the emetic toxin gene ces was not detected in any milk samples. In conclusion, the presenting of multi-virulent and β-lactam-resistant B. cereus in dried milk reinforce the need for improved hygiene during dairy processing. Future studies can employ whole-genome sequencing approaches to better understand the genetic diversity, and virulence mechanisms in B. cereus from dairy environments.